Development and characterisation of MMT-reinforced polyacrylonitrile-pullulan nanofibers for controlled permeation of isotretinoin - Badriyah Shadid Alotaibi; Qasim Talib Awan; Haya Yasin; Manal Buabeid; Saba Kaleem; Shamyla Nawazish; Abida Kalsoom Khan; Ghulam Murtaza (Journal of Experimental Nanoscience, 2023)
Drug nanofibers play a crucial role in ameliorating therapeutic effects, reducing toxicity, and increasing the bioavailability of drugs. This study was aimed at the fabrication of isotretinoin-loaded MMT-reinforced bi-polymeric (PAN/PU) nanofibers with varying concentrations of isotretinoin. In this study, montmorillonite (MMT)-reinforced cross-linked polyacrylonitrile and pullulan nanofibers combined with varying amounts of isotretinoin were fabricated through an electrospinning approach and investigated for their drug permeation potential. PAN-PU nanofibers were successfully integrated with the isotretinoin. The incorporation of isotretinoin into the nanofibrous structure was confirmed by FTIR and XRD. TGA study indicated the stability of the fabricated nanoparticles. The SEM results showed the beaded and smooth morphology of nanofibers. Formulation with a higher drug concentration had a non-significantly (p > 0.05) higher swelling ratio. Drug-loaded polymeric nanofiber erodes at a slower rate as compared to drug-free nanofibers. The ex-vivo permeation study of nanofibers revealed that the drug was not released all at once, but rather gradually and consistently over the period of 24 h, indicating a controlled release of the drug. In addition, the drug concentration in the nanofibers affected the permeation of the drug. According to the findings, isotretinoin-loaded MMT-reinforced bi-polymeric (PAN/PU) nanofibers with varying concentrations of isotretinoin were successfully fabricated. The fabricated nanofibers (PAN/PU) showed a promising potential for controlled permeation of drugs through rabbit skin.